Determinants of bank profitability in US and the impact of Basel III - ZHANG, ZHONGFANG (2019)
This paper examines the determinants of bank profitability in US from 2008 to 2018. In order to develop previous work, this paper also evaluate the impact of Basel III on bank profitability. The determinant variables are chosen from bank-specific and macroeconomic factors. The estimation results show that Basel III, capitalization, GDP growth and inflation contribute to higher profitability of banks. However, higher cost-in-come and size are associated with lower profitability. Besides, the relationship between liquidity and credit risk and profitability is not clear. Finally, this paper gives suggestons based on the empirical results.